2012
DOI: 10.1590/s1806-83242012005000005
|View full text |Cite
|
Sign up to set email alerts
|

Does the contact time of alginate with plaster cast influence its properties?

Abstract: The aim of this study was to verify the influence of the time of contact between alginate and gypsum after the modeling procedure on the properties of the plaster cast, such as surface detail, dimensional stability and microhardness. Thirty cylindrical specimens of orthodontic gypsum Type III were made by means of impressions of a stainless steel master model which had five reference lines in the upper surface. The samples were divided into two groups: Group 1 (G1) -with time of contact of 1 hour; and Group 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…For this reason, calcium sulphate dihydrate is usually used in alginate/gypsum-based dental impression mixtures as this enables slower calcium ion release and a controlled alginate setting time. On the other hand, it is also known [37,38] that alginate belongs to the gypsum setting time retarders, similarly as blood, saliva and agaragar, and reduces the number of crystallisation nuclei for the dihydrate particles. Therefore, it is not surprising that the setting time of the samples containing 5% alginate was extended by 5 minutes in comparison with the compositions without alginate.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, calcium sulphate dihydrate is usually used in alginate/gypsum-based dental impression mixtures as this enables slower calcium ion release and a controlled alginate setting time. On the other hand, it is also known [37,38] that alginate belongs to the gypsum setting time retarders, similarly as blood, saliva and agaragar, and reduces the number of crystallisation nuclei for the dihydrate particles. Therefore, it is not surprising that the setting time of the samples containing 5% alginate was extended by 5 minutes in comparison with the compositions without alginate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we need to discuss this issue with caution, and further studies are needed in this regard. The only similar study was done by Marquezan et al who investigated the effect of contact time (1 and 12 hours) between stone and alginate impression material, and it was found that increasing the contact time did not have any effect on the dimensional stability of the casts (8). Concerning the reasons for the difference in results between the latter and the present study can be attributed to the differences in the type of impression material used and the contact time between the stone and the impression (which were lower than the times tested in our study).…”
Section: Discussionmentioning
confidence: 97%
“…In order to make each prosthesis with good adaptation, it is important to have an accurate impression combined with a cast which has high dimensional stability (1,8). As previously mentioned, several factors are effective in producing dimensional accuracy of impressions and resultant casts.…”
Section: Discussionmentioning
confidence: 99%
“…From the results, they concluded that by expansion of the contact time between the above-said two dental materials, enhancement of hardness was achieved. The impact of the contact time between alginate and gypsum was assessed by Marquezan et al, 17 who demonstrated the techniques which affected the properties of cast models. They used 30 cylindrical stainless steel models which were used for making Type III gypsum.…”
Section: Discussionmentioning
confidence: 99%